OPTIMALISASI MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBASIS DIGITAL SEBAGAI UPAYA PENGUATAN PENDIDIKAN KARAKTER DI MADRASAH DINIYAH - Muzammil; Nur Laili (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This study aims to analyze the optimization of the digital-based Contextual Teaching and Learning (CTL) model in strengthening character education at Madrasah Diniyah Nurul Jadid. The background of this study is based on the demands of education in the digital era, which emphasize the importance of integrating cognitive aspects and character values within real-life contexts. This research employed a qualitative approach using a case study design, with data collected through observation, semi-structured interviews, and documentation techniques. The results showed that the implementation of digital-based CTL was carried out through the integration of contextual learning content supported by digital media, collaborative learning accompanied by inquiry activities, as well as reflection and authentic assessment. This implementation successfully shifted the learning pattern from teacher-centered to student-centered learning, thereby increasing students’ active engagement. Supporting factors included the availability of technological facilities, teachers’ competencies, and internet access, although limitations in facilities and network connectivity were addressed adaptively. The impact of this implementation indicated a significant improvement in students’ character development, marked by a reduction in inattentiveness and an increase in responsibility, discipline, independence, patience, and gratitude. Therefore, these findings confirm that digital-based CTL is proven to be an effective learning model that is integrative, reflective, and relevant for strengthening character education in the digital era. ABSTRAK Penelitian ini bertujuan untuk menganalisis optimalisasi model Contextual Teaching and Learning (CTL) berbasis digital dalam penguatan pendidikan karakter di Madrasah Diniyah Nurul Jadid. Latar belakang penelitian ini didasarkan pada tuntutan pendidikan di era digital yang menekankan pentingnya integrasi antara aspek kognitif dan nilai-nilai karakter dalam konteks kehidupan nyata. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus melalui teknik pengumpulan data observasi, wawancara semi-terstruktur, dan dokumentasi. Hasil penelitian menunjukkan bahwa implementasi CTL berbasis digital dilakukan melalui integrasi konten pembelajaran yang kontekstual dengan dukungan media digital, pembelajaran kolaboratif yang disertai inkuiri, serta refleksi dan penilaian autentik. Penerapan ini mampu menggeser pola pembelajaran dari yang berpusat pada guru menjadi berpusat pada siswa sehingga meningkatkan keterlibatan aktif siswa. Faktor pendukung meliputi ketersediaan sarana teknologi, kompetensi guru, dan akses internet, meskipun dihadapkan pada keterbatasan fasilitas dan jaringan yang diatasi secara adaptif. Dampak implementasi ini menunjukkan peningkatan signifikan terhadap karakter siswa, ditandai dengan penurunan ketidakfokusan serta peningkatan nilai tanggung jawab, disiplin, kemandirian, kesabaran, dan rasa syukur. Dengan demikian, temuan ini menegaskan bahwa CTL berbasis digital terbukti efektif sebagai model pembelajaran yang integratif, reflektif, dan relevan dalam penguatan pendidikan karakter di era digital.